An outbreak of Ralstonia pickettii endophthalmitis following intravitreal methotrexate injection - Choudhury H (Dove Medical Press, 2015)
Himadri Choudhury,1 Animesh Jindal,1 Avinash Pathengay,1 Harry W Flynn Jr21LV Prasad Eye Institute, GMR Varalakshmi Campus, Visakhapatnam, India; 2Department of Ophthalmology, Bascom Palmer Eye Institute, Miller School of Medicine, University of Miami, Miami, FL, USAPurpose: To report an outbreak of endophthalmitis in three eyes of two patients following intravitreal methotrexate, caused by Ralstonia pickettii.Design: Retrospective, noncomparative, consecutive case series.Methods: Medical records and microbiology results of two patients who presented with acute endophthalmitis following intravitreal methotrexate injection in November 2013 were reviewed.Results: Following intravitreal injections, the patients experienced pain and decrease in vision in the affected eye within 24 hours of receiving intravitreal methotrexate injection. The presenting visual acuity in case 1 was 20/50 in the left eye. The presenting visual acuity in case 2 was hand motions in the right eye and counting fingers at 1 m in the left eye. Both the patients received methotrexate prepared in the same manufacturing facility. Both the patients underwent vitreous biopsy and intravitreal injection of vancomycin 1 mg/0.1 mL, amikacin 400 µg/0.1 mL, and dexamethasone 400 µg/0.1 mL. Microbiology cultures from vitreous, and used and unused vials of methotrexate from the same batch grew R. pickettii. After 8 months of follow-up, both the patients had visual acuity 20/60 or better.Conclusion: R. pickettii can be rarely associated with outbreak of endophthalmitis. Timely intervention can be associated with good visual outcome in such patients.Keywords: Ralstonia pickettii, intravitreal injection, intravitreal methotrexate